Gamifying education: what makes a learning experience feel like a game? - Wan Tahir, Wan Mardyatul Miza (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Gamification in education enhances student engagement by integrating game-like elements into learning to increase motivation and deeper understanding. Instead of relying solely on traditional lectures and tests, gamified learning uses clear goals structured as missions or challenges aligned with long-term learning outcomes, distinguishing it from short-term game objectives. Effective gamification also incorporates rewards such as points and badges to motivate and track progress, along with immediate feedback mechanisms that help students adjust strategies, correct mistakes, and maintain engagement through a sense of flow.